Encapsulation of Oleuropein in Nanostructured Lipid Carriers: Biocompatibility and Antioxidant Efficacy in Lung Epithelial Cells - Amaia Huguet-Casquero; Maria Moreno-Sastre; Tania Belén López-Méndez; Eusebio Gainza; Jose Luis Pedraz (MDPI AG, 2020)
Oxidative damage has been linked to a number of diseases. Oleuropein (OLE), a natural occurring polyphenol from olive leaves (Olea europaea L.), is known to be a potent antioxidant compound with inherent instability and compromised bioavailability. Therefore, in this work, nanostructured lipid carriers (NLCs) were proposed for OLE encapsulation to protect and improve its antioxidant efficacy. The lipid matrix, composed of olive oil and Precirol, was optimized prior to OLE encapsulation. The characterization of the optimized oleuropein-loaded NLCs (NLC-OLE) showed a mean size of 150 nm, a zeta potential of −21 mV, an encapsulation efficiency of 99.12%, sustained release profile, and improved radical scavenging activity. The cellular in vitro assays demonstrated the biocompatibility of the NLCs, which were found to improve and maintain OLE antioxidant efficacy in the A549 and CuFi-1 lung epithelial cell lines, respectively. Overall, these findings suggest a promising potential of NLC-OLE to further design a pulmonary formulation for OLE delivery in lung epithelia.